FARMER'S INNOVATIVE ATTITUDE TO THE WORK ETHOS OF RICE FARMERS IN SABIANO VILLAGE, WUNDULAKO DISTRICT KOLAKA REGENCY - Salahuddin Salahuddin; Musadar Mappasomba; Muhammad Fadhil Pallatje; Nurhayu Malik (Fakultas Pertanian Universitas Halu Oleo, 2022)
This studied aimed to determine the innovative attitude, work ethic and the relationship between innovative attitudes and work ethic of rice farmers in Sabiano Village, Wundulako District, Kolaka Regency.This research was carried out in Sabiano Village, Wundulako District, Kolaka Regency. The population in this study were all rice farmers in Sabiano Village, Wundulako District as many as 110 people. The research sample amounted to 31 farmers. The sampling method is done by simple random sampling (simple random). The results of this studied indicated that the innovative attitude of farmers in the good category, the work ethic of farmers in the good category, and the innovative attitude of farmers have a positive significant relationship with the work ethic of lowland rice farmers in Sabiano Village, Wundulako District, Kolaka Regency.